The potential science and engineering value of samples delivered to Earth by Mars sample return: International MSR Objectives and Samples Team (iMOST). (5th March 2019) - Beaty, D. W.; Grady, M. M.; McSween, H. Y.; Sefton‐Nash, E.; Carrier, B. L.; Altieri, F.; Amelin, Y.; Ammannito, E.; Anand, M.; Benning, L. G.; Bishop, J. L.; Borg, L. E.; et al.
Abstract : Executive Summary: Return of samples from the surface of Mars has been a goal of the international Mars science community for many years. Affirmation by NASA and ESA of the importance of Mars exploration led the agencies to establish the international MSR Objectives and Samples Team (iMOST). The purpose of the team is to re‐evaluate and update the sample‐related science and engineering objectives of a Mars Sample Return (MSR) campaign. The iMOST team has also undertaken to define the measurements and the types of samples that can best address the objectives. Seven objectives have been defined for MSR, traceable through two decades of previously published international priorities. The first two objectives are further divided into sub‐objectives. Within the main part of the report, the importance to science and/or engineering of each objective is described, critical measurements that would address the objectives are specified, and the kinds of samples that would be most likely to carry key information are identified. These seven objectives provide a framework for demonstrating how the first set of returned Martian samples would impact future Martian science and exploration. They also have implications for how analogous investigations might be conducted for samples returned by future missions from other solar system bodies, especially those that may harbor biologically relevant or sensitive material, such as Ocean Worlds (Europa, Enceladus, Titan) and others. Summary of Objectives and Sub‐Objectives for MSR Identified by iMOST: Objective 1 Interpret the primary geologic processes and history that formed the Martian geologic record, with an emphasis on the role of water. Intent To investigate the geologic environment(s) represented at the Mars 2020 landing site, provide definitive geologic context for collected samples, and detail any characteristics that might relate to past biologic processes This objective is divided into five sub‐objectives that would apply at different landing sites. 1.1 Characterize the essential stratigraphic, sedimentologic, and facies variations of a sequence of Martian sedimentary rocks. Intent To understand the preserved Martian sedimentary record. Samples A suite of sedimentary rocks that span the range of variation. Importance Basic inputs into the history of water, climate change, and the possibility of life 1.2 Understand an ancient Martian hydrothermal system through study of its mineralization products and morphological expression. Intent To evaluate at least one potentially life‐bearing "habitable" environment Samples A suite of rocks formed and/or altered by hydrothermal fluids. Importance Identification of a potentially habitable geochemical environment with high preservation potential. 1.3 Understand the rocks and minerals representative of a deep subsurface groundwater environment. Intent To evaluate definitively the role of water in the subsurface. Samples Suites of rocks/veins representing water/rock interaction in the subsurface. Importance May constitute the longest‐lived habitable environments and a key to the hydrologic cycle. 1.4 Understand water/rock/atmosphere interactions at the Martian surface and how they have changed with time. Intent To constrain time‐variable factors necessary to preserve records of microbial life. Samples Regolith, paleosols, and evaporites. Importance Subaerial near‐surface processes could support and preserve microbial life. 1.5 Determine the petrogenesis of Martian igneous rocks in time and space. Intent To provide definitive characterization of igneous rocks on Mars. Samples Diverse suites of ancient igneous rocks. Importance Thermochemical record of the planet and nature of the interior. Objective 2 Assess and interpret the potential biological history of Mars, including assaying returned samples for the evidence of life. Intent To investigate the nature and extent of Martian habitability, the conditions and processes that supported or challenged life, how different environments might have influenced the preservation of biosignatures and created nonbiological "mimics, " and to look for biosignatures of past or present life. This objective has three sub‐objectives: 2.1 Assess and characterize carbon, including possible organic and pre‐biotic chemistry. Samples All samples collected as part of Objective 1. Importance Any biologic molecular scaffolding on Mars would likely be carbon‐based. 2.2 Assay for the presence of biosignatures of past life at sites that hosted habitable environments and could have preserved any biosignatures. Samples All samples collected as part of Objective 1. Importance Provides the means of discovering ancient life. 2.3 Assess the possibility that any life forms detected are alive, or were recently alive. Samples All samples collected as part of Objective 1. Importance Planetary protection, and arguably the most important scientific discovery possible. Objective 3 Quantitatively determine the evolutionary timeline of Mars. Intent To provide a radioisotope‐based time scale for major events, including magmatic, tectonic, fluvial, and impact events, and the formation of major sedimentary deposits and geomorphological features. Samples Ancient igneous rocks that bound critical stratigraphic intervals or correlate with crater‐dated surfaces. Importance Quantification of Martian geologic history. Objective 4 Constrain the inventory of Martian volatiles as a function of geologic time and determine the ways in which these volatiles have interacted with Mars as a geologic system. Intent To recognize and quantify the major roles that volatiles (in the atmosphere and in the hydrosphere) play in Martian geologic and possibly biologic evolution. Samples Current atmospheric gas, ancient atmospheric gas trapped in older rocks, and minerals that equilibrated with the ancient atmosphere. Importance Key to understanding climate and environmental evolution. Objective 5 Reconstruct the processes that have affected the origin and modification of the interior, including the crust, mantle, core and the evolution of the Martian dynamo. Intent To quantify processes that have shaped the planet's crust and underlying structure, including planetary differentiation, core segregation and state of the magnetic dynamo, and cratering. Samples Igneous, potentially magnetized rocks (both igneous and sedimentary) and impact‐generated samples. Importance Elucidate fundamental processes for comparative planetology. Objective 6 Understand and quantify the potential Martian environmental hazards to future human exploration and the terrestrial biosphere. Intent To define and mitigate an array of health risks related to the Martian environment associated with the potential future human exploration of Mars. Samples Fine‐grained dust and regolith samples. Importance Key input to planetary protection planning and astronaut health. Objective 7 Evaluate the type and distribution of in‐situ resources to support potential future Mars exploration. Intent To quantify the potential for obtaining Martian resources, including use of Martian materials as a source of water for human consumption, fuel production, building fabrication, and agriculture. Samples Regolith. Importance Production of simulants that will facilitate long‐term human presence on Mars. Summary of iMOST Findings: Several specific findings were identified during the iMOST study. While they are not explicit recommendations, we suggest that they should serve as guidelines for future decision making regarding planning of potential future MSR missions. The samples to be collected by the Mars 2020 (M‐2020) rover will be of sufficient size and quality to address and solve a wide variety of scientific questions. Samples, by definition, are a statistical representation of a larger entity. Our ability to interpret the source geologic units and processes by studying sample sub sets is highly dependent on the quality of the sample context. In the case of the M‐2020 samples, the context is expected to be excellent, and at multiple scales. (A) Regional and planetary context will be established by the on‐going work of the multi‐agency fleet of Mars orbiters. (B) Local context will be established at field area‐ to outcrop‐ to hand sample‐ to hand lens scale using the instruments carried by M‐2020. A significant fraction of the value of the MSR sample collection would come from its organization into sample suites, which are small groupings of samples designed to represent key aspects of geologic or geochemical variation. If the Mars 2020 rover acquires a scientifically well‐chosen set of samples, with sufficient geological diversity, and if those samples were returned to Earth, then major progress can be expected on all seven of the objectives proposed in this study, regardless of the final choice of landing site. The specifics of which parts of Objective 1 could be achieved would be different at each of the final three candidate landing sites, but some combination of critically important progress could be made at any of them. An aspect of the search for evidence of life is that we do not know in advance how evidence for Martian life would be preserved in the geologic record. In order for the returned samples to be most useful for both understanding geologic processes (Objective 1) and the search for life (Objective 2), the sample collection should contain BOTH typical and unusual samples from the rock units explored. This consideration should be incorporated into sample selection and the design of the suites. The retrieval missions of a MSR campaign should (1) minimize stray magnetic fields to which the samples would be exposed and carry a magnetic witness plate to record exposure, (2) collect and return atmospheric gas sample(s), and (3) collect additional dust and/or regolith sample mass if possible.